Possibility of increased general health related problems in women involved in beedi rolling - Hegde, Divya; Kamath, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Beedis is an indigenous cigarette filled with tobacco flake and wrapped in a tendu leaf, tied with a string at one end. Beedis accounted for about 73% of Indian tobacco consumption (Chaudhry K, Rath GK. Multisectoral and intersectoral approach to national tobacco control. Paper commissioned by the World Health Organization on the occasion of the WHO international conference on global tobacco control law: towards a WHO framework convention on tobacco control. 2000 Jan 7-9, New Delhi, India). Over three million Indians of whom are women are employed as beedi rollers as a cottage industry (http://en.wikipedia.org/wiki/Beedi). A single woman on an average rolls 1000 beedies per day, using around 500 grams of tobacco flake. A beedi roller may in the process inhale tobacco dust and other volatile components. India tops in beedi consumption, followed by other south East Asian countries.Beedis are also exported to western countries were they are marketed in various flavors and are popular among middle school and high school students. The popular belief among teenagers in the west is that beedi is herbal and hence cannot cause cancer.